Using the Ferrenberg-Swendsen Monte Carlo method for nonuniversal exponents - Chahine, J. [UNESP]; Drugowich de Felício, J. R.; Caticha, N. (Elsevier B.V., 1989)
We use the method of Monte Carlo evolution in the coupling constant space of Ferrenberg and Swendsen to evaluate the nonuniversal exponent η* associated to a linear defect in a 2d Ising model. © 1989.